2009
DOI: 10.1002/lapl.200910006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and compact diode-pumped Q-switched Nd:GdVO4/LBO red laser

Abstract: At the same resonator experimental laser setup, we replace the AO to obtain the continuous-wave (CW) red laser. Fig. 2 shows the average output power for AO Qswitching operation versus the incident pump power at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…So the conversion efficiency will be improved to a certain degree. In [12,13], in high repetition rate in more than kHz, similar conclusion was reported.…”
Section: Methodssupporting
confidence: 90%
“…So the conversion efficiency will be improved to a certain degree. In [12,13], in high repetition rate in more than kHz, similar conclusion was reported.…”
Section: Methodssupporting
confidence: 90%
“…Although the nonlinear coefficient of LBO is 0.82 pm/V, the length of LBO could be extended to compensate the relatively smaller value of the nonlinear coefficient. The size of the LBO crystal is 3×3×15 mm 3 and both end faces were coated with AR film at 914 nm, 1047 nm, and 488 nm wavelengths. It was wrapped with a thin indium foil and mounted in a copper holder, which was cooled by a thermoelectric cooler for an active temperature control with the stability of ±0.1…”
Section: Methodsmentioning
confidence: 99%
“…Another vanadate crystal, Nd:GdVO 4 , which was confirmed to be supe rior to Nd:YVO 4 in thermal properties, was also inves tigated extensively. The research to output wavelengths involving Nd:GdVO 4 crystals were mostly focused at 1063 nm [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], 1341 nm [31][32][33][34][35][36][37], and 912 nm [38][39][40][41][42][43]. However, through the analysis of a spectroscopic study has demonstrated that there are three or four emission bands on the F 3/2 -I 11/2 transition of Nd:GdVO 4 crystal.…”
Section: Introductionmentioning
confidence: 99%